2021
DOI: 10.1111/ced.14689
|View full text |Cite
|
Sign up to set email alerts
|

The chameleon rash: a review of the polyphenotypic dermatoses of dermatomyositis

Abstract: Dermatomyositis (DM) is an autoimmune connective tissue disease that is included in the idiopathic inflammatory myopathies. Cutaneous manifestations are a prominent part of the condition: some skin signs in DM are common to most patients, while other signs are encountered infrequently. A number of features are pathognomic for DM. The demonstration of myositis-specific antibodies (MSAs) in DM has extended the ability to define phenotypic subgroups. It appears that the presence of certain MSAs confers susceptibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Gottron papule, heliotrope rash and V sign are the prominent characteristics of DM [13]. A single-center study involving 779 patients with IIM found that infection was more common in patients with dermatomyositis than in those with polymyositis, and they also found that a heliotrope rash is a risk factor for infection [14]. This nding supported symptom status as a key predictor of infection.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Gottron papule, heliotrope rash and V sign are the prominent characteristics of DM [13]. A single-center study involving 779 patients with IIM found that infection was more common in patients with dermatomyositis than in those with polymyositis, and they also found that a heliotrope rash is a risk factor for infection [14]. This nding supported symptom status as a key predictor of infection.…”
Section: Discussionmentioning
confidence: 85%
“…Several studies have indicated that ILD is an independent risk factor for infection. [14][15] Interestingly, we found a reduced risk of infection in patients who were positive for anti-Jo1 antibodies. This was consistent with the research of Yongpeng et al [14].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Dermatomyositis is an autoimmune connective tissue disease with heterogeneous cutaneous and muscular manifestations. 1 Cases of dermatomyositis emerging in association with SARS-CoV-2 vaccination are rare, with most cutaneous reactions to these vaccines now recognised as infrequent and transient. 2 Herein we report a case of a young, previously well female with rapid onset of classic dermatomyositis signs and symptoms after such vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…Dermatomyositis is an autoimmune connective tissue disease with heterogeneous cutaneous and muscular manifestations 1 . Cases of dermatomyositis emerging in association with SARS‐CoV‐2 vaccination are rare, with most cutaneous reactions to these vaccines now recognised as infrequent and transient 2 .…”
Section: Introductionmentioning
confidence: 99%